Analisis Pengelolaan Wakaf Uang Melalui Cash Waqf Linked Sukuk Dalam Meningkatkan Pemberdayaan Masyarakat - Larasati Dhinarti Nurresi Putri; Mira Rahmi; Prima Dwi Priyatno (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This research aims to identify and analyze cash waqf management system and management of CWLS program in improving community empowerment at Indonesian Waqf Board (BWI). This research uses descriptive qualitative method with case study approach, starting with interviewing BWI and Achmad Wardi Eye Hospital. Then to prove validity of research data, researcher used technique triangulation method. Furthermore, researcher analyzed data by doing data reduction, data presentation, and concluding. The results of research show that management of cash waqf carried out by BWI is quite diverse so that scopes becomes wide. Management of CWLS has been running according to set plan, but not all CWLS programs are run by BWI, there are several programs whose benefits are distributed to nazhir institutions registered by BWI.Keywords: Cash Waqf, CWLS, Community Empowerment, Management